New species and subspecies of Rhyacophila (Trichoptera: Rhyacophilidae) from Asia - Kiss, Ottó (Zootaxa, 2014)
New species and subspecies of the genus Rhyacophila (Trichoptera, Rhyacophilidae), i.e. Rhyacophila mikusi n. sp. in the R. yosiiana Group from Taiwan (Republic of China), Rhyacophila wichardi n. sp. in the R. curvata Group, Rhyacophila chayulpa ghunsa new subspecies in the R. chayulpa Group, and Rhyacophila chembo bigu new subspecies in the R. khimbarpa Group from Nepal are described and illustrated with drawings of the genitalia.